Bilateral internal mammary artery grafting in South America - Rojas, Pedro (2022)
Coronary artery bypass using bilateral internal thoracic artery (BITA) has been related to survival benefits in patients with coronary artery disease, but data is not conclusive. In South America, several centers reported their own experience with good results in survival, minimal postoperative cardiovascular events, and a low degree of mediastinal infection, however, the number of cases is low, and the absence of publications in several countries is a matter of concern. We review the leading publications on BITA grafting in our region, assessing how far we have advanced in coronary surgery.